2011
DOI: 10.1186/1475-2891-10-66
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preoperative feeding with a whey protein plus carbohydrate drink on the acute phase response and insulin resistance. A randomized trial

Abstract: BackgroundProlonged preoperative fasting increases insulin resistance and current evidence recommends carbohydrate (CHO) drinks 2 hours before surgery. Our hypothesis is that the addition of whey protein to a CHO-based drink not only reduces the inflammatory response but also diminish insulin resistance.MethodsSeventeen patients scheduled to cholecystectomy or inguinal herniorraphy were randomized and given 474 ml and 237 ml of water (CO group) or a drink containing CHO and milk whey protein (CHO-P group) resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
89
2
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(113 citation statements)
references
References 33 publications
12
89
2
10
Order By: Relevance
“…Comparison between first treatment group and control group shown increase of blood glucose level significant higher in control groups than in first treatment group (p=0.041). This is appropriate with the research by Perrone, et al conclude that increase of the blood glucose level lower in sample groups who got oral glucose solution on the night and morning before surgery than placebo groups [6]. This result shown that administration of oral glucose solution preoperatively, especially twice on the night and morning give significant effect on lowering the increase of blood glucose level postoperative.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Comparison between first treatment group and control group shown increase of blood glucose level significant higher in control groups than in first treatment group (p=0.041). This is appropriate with the research by Perrone, et al conclude that increase of the blood glucose level lower in sample groups who got oral glucose solution on the night and morning before surgery than placebo groups [6]. This result shown that administration of oral glucose solution preoperatively, especially twice on the night and morning give significant effect on lowering the increase of blood glucose level postoperative.…”
Section: Discussionsupporting
confidence: 71%
“…Study from Mathur et al in New Zealand, conducted in two groups of patients undergoing elective major abdominal surgery, this study showed the decrease of cortisol level was significantly lower in the group given oral glucose preoperatively on the night and two hours in the morning before induction than the group of patients given placebo on the first postoperative day [6].…”
Section: International Journal Of Anesthesiology and Pain Medicine Issnmentioning
confidence: 98%
“…The physiological consequences of intake of carbohydraterich sip drinks up to 2 hours before surgery are an up to 50% reduction in insulin resistance, which in turn shortens hospital stay and reduces postoperative complications; [6,8] lower muscle catabolism; [911] improved intraoperative haemodynamic stability, particularly in children, as a result of more favourable fluid balance status; reduced days to discharge fitness; and superior handgrip strength, a sensitive marker of early muscle protein loss. Perrone et al, [12] in a small study in 2011, showed that the addition of whey protein to a carbohydrate drink further improved insulin sensitivity and reduced acutephase markers compared with carbohydrate alone. In addition, benefits on various aspects of patient comfort (such as thirst and anxiety), cooperation, compliance and overall subjective satisfaction have been reported.…”
Section: Clinical Benefitsmentioning
confidence: 99%
“…17 In contrast, in a randomized study from Brazil of gastrointestinal surgery, the addition of whey protein to the carbohydrate drink appeared to have some added value in terms of reduced inflammatory response and lesser insulin resistance. 18 The benefits of the ERAS approach to colorectal surgery have been confirmed in several reports. 19,20,21 It can extend for a significant period after surgery.…”
Section: Current Approachesmentioning
confidence: 62%